Site occupancy and photoluminescence tuning of La3Si6−xAlxN11−x/3:Ce3+ phosphors for high power white light-emitting diodes. Issue 21 (21st April 2017) - Du, Fu; Zhuang, Weidong; Liu, Ronghui; Zhong, Jiyou; Liu, Yuanhong; Hu, Yunsheng; Gao, Wei; Zhang, Xia; Chen, Lei; Lin, Kun
Abstract : A series of phase pure nitride yellow phosphors La3 Si6− x Al x N11− x /3 :Ce 3+ with interesting spectrum red shifts and good thermal stability properties were synthesized, and the relationship between the luminous efficiency and the crystal structure were investigated in detail. Abstract : A series of blue light excitable yellow-emitting La3 Si6− x Al x N11− x /3 :Ce 3+ ( x = 0, 0.02, 0.04, 0.06, 0.08, and 0.1) phosphors were prepared by a high temperature solid state reactions method. The variations in micro-structure and luminescent properties induced by substituting the Al 3+ /Si 4+ ratio in La3 Si6− x Al x N11− x /3 :Ce 3+ and the related mechanism were investigated. Interestingly, the emission spectrum displayed a red-shift by strengthening the longer wavelength component of the spectrum instead of shifting the emission peak, which was verified to be ascribed to the changed site occupancy of Ce 3+ . The inducement of redistribution of Ce 3+ by introduction of Al 3+ as well as its influence on local structures were explored. A tunable spectrum could be obtained through controlling the entering rate of Ce 3+ at two different sites. The color rendering index of this phosphor system could be greatly improved with sufficient emission efficiency and thermal stability for applications in high power white light-emitting diodes.